The copper argyrodites Cu7-nPS6-nBrn: Crystal growth, structures and ionic conductivity - Pogodin Artem; Погодін Артем; Filep Mykhailo; Філеп Михайло; Filep Mihály; Malakhovska Tetyana; Малаховська Тетяна; Sabov Marjan; Сабов Мар’ян; Szabó Marján; Sidey Vasyl; Сідей Василь; et al. (Elsevier, 2019)
Abstract. Single crystals of the copper-containing Cu7-nPS6-nBrn (0 ≤ n ≤ 1) argyrodites have been grown by direct solidification using the Bridgman–Stockbarger technique. All compounds have been structurally characterized using the X-ray powder diffraction technique. Compositional dependencies of electrical conductivity and activation energy were studied. Two simple structural indicators have been proposed in order to predict the ionic conductivity in argyrodites under investigations. Interrelation between structure and mechanism of ionic conductivity was discussed.
Contents: https://www.sciencedirect.com/journal/solid-state-ionics/vol/341/suppl/C Editorial board: https://www.sciencedirect.com/journal/solid-state-ionics/about/editorial-board
Keywords: Argyrodites; Crystal growth; Structure; Ionic conductivity; Activation energy; Compositional dependence